EFEKTIVITAS PENGELOLAAN DANA KREDIT USAHA RAKYAT (KUR) DI BRI UNIT CAKKE BAGI PETANI BAWANG MERAH DI KECAMATAN ANGGERAJA KABUPATEN ENREKANG - Hariani, Ervina; Fatmawati, Fatmawati; Parawangi, Anwar (Universitas Muhammadiyah Makassar, 2022)
Effectiveness of People's Business Credit Fund Management for Shallot Farmers At BRI Cakke Unit, Anggeraja District, Enrekang Regency, where the problem arises is the lack of capital owned by shallot farmers to develop their onion farming business.The purpose of this study was to determine the Effectiveness of the Management of People's Business Credit Funds for shallot farmers to improve the welfare of the community in Anggeraja District, Enrekang Regency. The basis of the research used is descriptive qualitative, namely the author conducts interviews with informants, the source of the data itself is from primary data obtained through observation, interviews and documentation, while secondary data is obtained from documents, notes, reports. The results of this study indicate that the results obtained by shallot farmers according to the habits of the local community have increased in yields. Agricultural products have provided many benefits for the welfare of farmers. Income obtained from agricultural products can meet daily needs, education costs, health, to the fulfillment of housing needs so that it has a major influence on the development of the economic sector in Anggeraja District, Enrekang Regency.